A feasible and environmentally friendly method to simultaneously synthesize MoS2 quantum dots and pore-rich monolayer MoS2 for hydrogen evolution reaction. (1st January 2020) - Zhou, Qiulan; Luo, Xiaohu; Li, Yali; Nan, Yanxia; Deng, Haoyun; Ou, Encai; Xu, Weijian
Abstract: MoS2 has been one of a widely researched hydrogen evolution reaction (HER) catalyst materials in recent years. However, the basal plane of MoS2 is considered to be inactive to hinder its further development. Herein, a new mass-scalable and facile intercalation method for the fabrication of multiple products, including pore-rich monolayer MoS2 (PR MoS2 ) and MoS2 quantum dots (MoS2 QDs), has been developed via the gas phase etching of bulk MoS2 in an acetone vapor atmosphere. The obtained monolayer MoS2 QDs with a narrow lateral size distribution (average size: 2.5 nm) present excitation-independent photoluminescence emission. Furthermore, the PR MoS2 shows a significantly enhanced HER electrocatalytic activity and good stability in 0.5 M H2 SO4 solution with a small overpotential of 241 mV at a current density of 10 mA cm −2 . These results demonstrate that the as-prepared PR MoS2 is very promising for the application in HER. Graphical abstract: Image 1 Highlights: MoS2 quantum dots and pore-rich monolayer MoS2 are simultaneously synthesized. 2H–MoS2, 1T-MoS2 and amorphous MoS2 coexist in pore-rich monolayer MoS2. Pore-rich structure and different phases provide enormous active edge defects. Pore-rich monolayer MoS2 shows better HER performance than bulk MoS2 .